Histological Changes of the Ovary in Pregnant Mice Vaginally Exposed to Toxoplasma gondii - Zahra Eslamirad; Parvin Dokht Bayat; Saeid Babaei (Iranian Journal of Parasitology, 2015)
Background:Congenital toxoplasmosis is one cause of abortion. Infection can disrupt ovarian cycles and because toxoplasmosis is an infectious disease may have a similar effect on the ovaries. The purpose of this study was to investigate the pathological changes in the ovaries due to toxoplasmosis. Methods:Tachyzoites of Toxoplasma gondii were harvested from peritoneal fluid of mice, experimentally infected. Two females and one male mouse were housed per cage for mating in the overnight. The pregnant mice were divided into experi-mental and control groups. Experimental group were infected by parasite but the control group received the normal saline. The experimental and control mice were euthanized. Ovaries and uterine horns of animals were removed and prepared for light microscopy. Results:Ovaries of infected pregnant mice presented gross morphological differ-ences compared to the control groups. In ovaries of experimental groups, changes of corpus luteum were observed. The comparison of experimental and control groups revealed that the number of primary follicles, secondary follicle, atretic pri-mary follicles and atretic secondary follicles had significant differences (P≤0.001). Conclusion:Toxoplasma gondii alters ovarian follicular growth and development in mice. In addition, it alters number of different phases of follicles and corpus lu-teum in ovaries of mice.